Torta de girassol na alimentação de frangos de corte - Berwanger, Eveline (2013)
Four experiments were conducted in order to carry out the assessment of nutritional sunflower cake for broilers. The Sunflower cake samples used in the experiments were submitted bromatological analysis. The first study aimed to evaluate the energy values of sunflower cake for broilers using the method of total excreta collection. For this work were used 100 broiler chickens 21-31 days old. The birds were fed diets containing 10, 20, 30 and 40% inclusion of sunflower cake in a reference diet (kg / kg), and each treatment consisted of 4 replicates. After the experimental period, the feces were dried, and then analyzed, thereby obtaining energy values and total nitrogen. With these results were calculated apparent metabolizable energy and apparent metabolizable energy corrected for nitrogen balance and its coefficients. The second experiment evaluated the influence of the period and amount of sunflower cake provided to cockerels on the digestibility of amino acids. The birds were divided into three treatments, which corresponded to supply 30 g of sunflower cake (15 g with an interval of 12 h), providing 30 g of sunflower cake (15 g with an interval of 24 h), and only 15 g of sunflower cake through forced feeding technique. Alongside the treatments, 6 roosters were fasted for 56 h of collection period cocks under treatment for correction of metabolic and endogenous losses. Samplings were made of the excreta and after the end of the experiment the samples were sent for analysis of amino acids using HPLC. The results of digestibility coefficients were subjected to Tukey's test. In the third and fourth experiment we evaluated the performance and carcass yield and cuts, as well as the intestinal morphology and viability of inclusion of sunflower cake in the feed of broilers at different stages. In these experiments, the birds were distributed in a completely randomized design. We used a 2x5 factorial arrangement, with five levels of inclusion of sunflower cake (0, 5, 10, 15, and 20% in the diet), with or without the addition of enzyme complex. The third experiment evaluated these treatments during 1-21 days of age and the total period of 1 to 42 days, but 22-42 days of age, these animals received the same diet (growing and finishing). In the fourth experiment the inclusion of sunflower cake in the diet was tested for broilers during 22 to 42 days old. Statistical analyzes used were variance analysis will, polynomial regression and Dunnett test will 5% probability. The chemical composition observed for sunflower cake was 92.17% DM, 24.37% CP, 23.80% EE, 35.32% NDF, 22.30% ADF, 4.10% MM, 0.725% Calcium, 0.228% total phosphorus and 4,819 Kcal.Kg EB-1. The AME, AMEn, CMA and CMAN for sunflower cake were 2211.68 kcal / kg, 2150.54 kcal / kg, 45.47% and 44.73%, respectively. The amino acids digestibility coefficient (ADC) evaluated in the second experiment was changed due to the amount of food provided in the feeding method, and when used only 15 g, ADC values were underestimated. The lysine, histidine and threonine amino acids were at lower digestibility, and arginine and methionine showed the highest digestibility of sunflower cake for birds. The results of the third and fourth experiments showed no interaction between inclusion level and enzymes to the parameters evaluated. In experiment III, for the results at 21 days, there was no effect (P> 0.05) enzyme only on the productive efficiency. However, considering the inclusion levels, weight gain, final weight and feed intake decrease showed linear (P <0.05) with increasing level of inclusion of sunflower cake. These birds at 42 days of age, were not influenced by levels of performance results, however, with the use of enzymes, the animals showed better results (P <.05). Carcass yield decreased, and conversely, abdominal fat increased with the inclusion of the pie until 21 days of age. The enzyme improved the yield of thigh, chest and housing. The duodenum and ileum of broilers at 21 days of age showed a decrease in villus height. The jejunum and duodenum showed increased crypt depth. The three segments of the intestine decreased (P <0.05) the villus: crypt with increasing level of inclusion of sunflower cake in the diet, which could have harmed the growth of the birds during 1-21 days of age. The economic viability from 1 to 21 days and 1 to 42 days showed that the 0% level was the best economic result, but the 5% level equaled (P> 0.05) at 0%. In the fourth experiment, feeding the birds 22-42 days of age, increased with increasing levels of inclusion of sunflower cake in the diet. There was no effect of any of the variables tested for carcass yield, cuts and offal, however, for the carcass, diets with inclusion from 15% differed (P <0.05) than the control treatment. There was no effect of enzymes, which increased the yield of carcass and breast yield and decreased thigh and wings. Segments affected by the diets containing sunflower cake were the jejunum and ileum, thus impairing absorption of nutrients, and consequently the results of performance of broilers. The best results were found in the economic viability to the level of 0% (control)